Prevention in pieces: representing conflict in the Women, Peace and Security agenda. Issue 4 (20th October 2017) - Basu, Soumita; Shepherd, Laura J.
ABSTRACT: The Women, Peace and Security agenda is often operationalized across three priority areas: the participation of women in peace and security governance; the protection of women's rights and bodies (specifically, but not limited to, conflict-related sexual violence); and the prevention of conflict. In this short paper, we explore violence prevention in more detail, and argue that it is of critical importance to define conflict as well as prevention. We draw on the illustrative examples of Australia, the UK and India to explain how this definitional work happens within the machinery of the state and the networks of civil society. Understanding how conflict is theorized by different actors in different locations not only gives insight into the tendency towards militarization in the WPS agenda but also can be interpreted as a manifestation of contestation over ownership of the WPS agenda and its location between the state and civil society.